Boron/nitrogen co-doped carbon synthesized from waterborne polyurethane and graphene oxide composite for supercapacitors. Issue 3 (14th January 2019) - Li, Rui; Qin, Chuanli; Zhang, Xuxu; Lin, Zitong; Lv, Shixian; Jiang, Xiankai
Abstract : We report B/N co-doped carbon materials synthesized by a carbonization method with ferric catalyst treatment from a precursor with boric acid treatment after the formation of the composite between waterborne polyurethane and graphene oxide. Abstract : We report B/N co-doped carbon materials synthesized by an efficient and easy one-step carbonization method with ferric catalyst treatment from a precursor with boric acid treatment after the formation of the composite between waterborne polyurethane (WPU) and graphene oxide (GO). The nitrogen content was improved with the introduction of numerous melamine in the synthetic process of WPU. In addition, WPU possessed a repetitive basic unit urethane bond (–NHCOO); thus, nitrogen heteroatom could be efficiently introduced into the WPU/GO composite from WPU as a nitrogen-rich carbon. In addition, the specific surface area was increased by the boric acid treatment and washing process. The ferric catalyst treatment could prevent the formation of inert B–N bonds. Thus, the synthesized B/N co-doped carbon materials exhibited high specific capacitance (330 F g −1 at 0.5 A g −1 ), superior rate performance, and excellent cycling stability. Furthermore, the assembled symmetric supercapacitor displayed a good energy density (7.9 W h kg −1 at 505 W kg −1 ) and a good capacitance retention of about 89.9% after 5000 charge–discharge cycles in 6 M KOH electrolyte. Therefore, the as-prepared B/N co-doped carbon materials show a promising future in supercapacitor application.